An Approach to Determine the Attributes of Shadow Under Artificial Lighting - Aydin Yagmur, Sensin; Dokuzer Ozturk, Leyla (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
The attributes of shadows produced in architectural spaces is one criterion of lighting design. A shadow has two different attributes; harshness-softness and lightness-darkness. The project entitled An approach for definition and evaluation of shadow characteristics as a design criterion occured under artificial lighting (2011-03-01-DOP01) was implemented at Yildiz Technical University to develop an approach for determining and quantifying the characteristics of shadow. For this purpose, the two attributes of cast shadows were treated separately. This study presents the procedures and results of the project regarding the definition and grading of the harshness-softness attribute of shadows.
Keywords: Umbra; shadow factor; shadow attributes; penumbra; harsh shadow; soft shadow; Architecture